Cholesterol effects on the phosphatidylcholine bilayer polar region: a molecular simulation study. - Pasenkiewicz-Gierula, M (2000)
A molecular dynamics (MD) simulation of a fully hydrated, liquid-crystalline dimyristoylphosphatidylcholine (DMPC)-Chol bilayer membrane containing approximately 22 mol% Chol was carried out for 4.3 ns. The bilayer reached thermal equilibrium after 2.3 ns of MD simulation. A 2.0-ns trajectory generated during 2.3-4.3 ns of MD simulation was used for analyses to determine the effects of Chol on the membrane/water interfacial region. In this region, 70% of Chol molecules are linked to DMPC molecules via short-distance interactions, where the Chol hydroxyl group (OH-Chol) is 1) charge paired to methyl groups of the DMPC choline moiety ( approximately 34%), via the hydroxyl oxygen atom (Och); 2) water bridged to carbonyl ( approximately 19%) and nonester phosphate ( approximately 14%) oxygen atoms, via both Och and the hydroxyl hydrogen atom (Hch); and 3) directly hydrogen (H) bonded to carbonyl ( approximately 11%) and nonester phosphate ( approximately 5%) oxygen atoms, via Hch ( approximately 17% of DMPC-Chol links are multiple). DMPC's gamma-chain carbonyl oxygen atom is involved in 44% of water bridges and 51% of direct H bonds formed between DMPC and Chol. On average, a Chol molecule forms 0.9 links with DMPC molecules, while a DMPC molecule forms 2.2 and 0.3 links with DMPC and Chol molecules, respectively. OH-Chol makes hydrogen bonds with 1.1 water molecules, preferentially via Hch. The average number of water molecules H bonded to the DMPC headgroup is increased by 7% in the presence of Chol. These results indicate that inclusion of Chol decreases interlipid links and increases hydration in the polar region of the membrane.